Communication Redefined: Natural Language Processing in the Digital Age - Nishat, Atika; Mustafa, Areej (MZ Journal of Artificial Intelligence, 2024)
This paper talks about the developmental role of Natural Language Processing (NLP) in shaping communication in the digital era. NLP, a branch of artificial intelligence, is devoted to the programming of computers so that they understand, interpret, and generate human language, thereby changing the way we interact with information and technology in a revolutionary manner. This paper gives an insightful look into the basic principles, latest developments, and the pragmatic applications of NLP in communication. This has been happened from early rule-based systems to the current deep learning models, the evolution of NLP has led to machines being able to understand and generate language with increasing accuracy and complexity.